National-cultural self-determination of ethnic communities of the Kabardino-Balkarian Republic as a component of Russian civil identity - Svetlana I. Akkieva; Asiyat R. R (Кавказология, 2023)
The study investigates the phenomena of national-cultural self-determination of Kabardino-Balkarian Republic ethnic communities in the framework of Russian civic identity. The main directions of scientific research devoted to national-cultural self-determination and its relationship with civil identity are examined, as well as how the wide diversity of the ethnic composition of the country’s population or its individual region necessarily places the task of maintaining stability in the sphere of interethnic relations on the shoulders of the leadership. The Kabardino-Balkarian Republic’s legal backing and control of national relations, as well as the operation of national cultural centers, are discussed. Particular emphasis is placed on the activities of the Kabardino-Balkarian Republic’s Ministry of National Affairs and public projects aimed at achieving civil, interethnic, and interfaith harmony in the region.